2019
DOI: 10.1021/acsami.8b20454
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Fuel Cell Based on New Nanocrystalline Structure Gd0.1Ce0.9O2 Electrolyte

Abstract: Lowering the operating temperature is a universal R&D challenge for the development of low-temperature (<600 °C) solid oxide fuel cells (SOFCs) that meet the demands of commercialization. Regarding the traditional electrolyte materials of SOFCs, bulk diffusion is the main ionic conduction mechanism, which is primarily affected by the bulk density and operating temperatures. In this study, we report a new mechanism for the Ce 0.9 Gd 0.1 O 2-δ (GDC) electrolyte based on a nanocrystalline structure with surface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 45 publications
3
59
0
Order By: Relevance
“…Figure 5a,b shows I-V and I-P characteristics for single cells with nanocrystalline structure CeO 2 and SNDC electrolytes and the corresponding simple schematic diagram of the cell. As reported previously, the open circuit voltages (OCVs) of cells increase rapidly at the beginning of the test and then stays above 1 V, which is closed to the value of SOFC reported in the literature [21], indicating that the nanoelectrolytes are effective at separating H 2 and air from each side of the cell. The achieved OCVs of the cell for the nanocrystalline structure SNDC electrolyte (Figure 5a) reach the 1.154, 1.148 and 1.141 V at 450, 500 and 550 • C, respectively, which are more than those (1.14, 1.133 and 1.078 V at corresponding temperatures) of cell with the nanocrystalline structure CeO 2 electrolyte (Figure 5b).…”
Section: Fuel Cell Performance Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…Figure 5a,b shows I-V and I-P characteristics for single cells with nanocrystalline structure CeO 2 and SNDC electrolytes and the corresponding simple schematic diagram of the cell. As reported previously, the open circuit voltages (OCVs) of cells increase rapidly at the beginning of the test and then stays above 1 V, which is closed to the value of SOFC reported in the literature [21], indicating that the nanoelectrolytes are effective at separating H 2 and air from each side of the cell. The achieved OCVs of the cell for the nanocrystalline structure SNDC electrolyte (Figure 5a) reach the 1.154, 1.148 and 1.141 V at 450, 500 and 550 • C, respectively, which are more than those (1.14, 1.133 and 1.078 V at corresponding temperatures) of cell with the nanocrystalline structure CeO 2 electrolyte (Figure 5b).…”
Section: Fuel Cell Performance Analysissupporting
confidence: 80%
“…Takamura [20] prepared the CeO 2 -based nanoparticles and acquired the conductivity of 0.003 S•cm −1 at the low temperature (300 • C). Chen et al [21] reported that the nanocrystalline GDC electrolyte generated a remarkable power out of 591.8 mWcm −2 with extraordinary ionic conductivity of 0.37 S•cm −1 at 550 • C. The out performance is more than 3 times higher than that of traditional high-temperature sintered GDC electrolyte. The nanocrystalline electrolyte has presented unexceptionable properties as compared to the conventional electrolyte, which revealed that the interface/surface conduction of nanocrystalline GDC electrolyte was critical in improving ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The specic preparation methods have been reported in the literature. 34 The GDC and SCY electrolyte pellets were pressed at 100 MPa and sintered at 1550 and 1600 C for 5 h. Fig. 5(a) shows a schematic illustration of the cells with a GDC/STO and SCY/STO dual electrolyte, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[19] Grain boundary resistance can be further minimized by fabricating highly textured yttrium-doped barium zirconate thin films with a grain-boundary-free structure through epitaxial growth or pulsed laser deposition. [20,21] Gang et al revealed that ionic interface conduction, or surface diffusion, is the main ionic conduction mechanism in nanocrystalline Ce 0.8 Gd 0.2 O 2 [22] and BaZr 0.9 Y 0.1 O 3Àδ [23] at high temperatures.…”
Section: Introductionmentioning
confidence: 99%